"How-to" - Unidentified artist (Colorado State University. Libraries, 1980)
A section of a mola that is under construction.
How-to
This item was part of an exhibition at the Avenir Museum of Design and Merchandising titled Kuna Molas: Sewn Stories and the Interplay of Tradition and Change, August 18, 2014-July 31, 2015.
Cotton; 3 layers (maroon, yellow-orange, orange); reverse appliqué.
Keywords: Molas -- Panama; Appliqué -- Panama; Embroidery -- Panama